Synthesis of Willow Leaves and Apricot Leaves-based Carbon Quantum Dots Fluorescent Probes and their Applications in Biosensing - Wen, He (UNIMAS, 2025)
Metal cations and biomolecules are essential for a wide range of physiological processes. The unique nanostructure of carbon quantum dots (CQDs) gives them excellent fluorescence properties and biocompatibility as fluorescent probes, which have great potential for applications in biosensing. However, current research on CQDs as fluorescent probes faces three major challenges: the use of unsafe and toxic chemical raw materials, low quantum yield, and low accuracy. A technique was devised to synthesize CQDs fluorescent probes from non-toxic willow leaves. An experiment was conducted for 12 h at a pH of 7.4 and a temperature of 200°C. Based on the ability of Cu²⁺ ions to form a complex with CQDs and pyrophosphate (PPi), an "off-on-off" fluorescent probe was developed. This probe enables the selective detection of pyrophosphatase (PPase) with a CQDs dosage of 50 µL, a PPi concentration of 5.0×10⁻⁴ mol/L, and a response time of 40 min. The results indicated that the linearity of PPase was satisfactory within the range of 0 to 0.8 U/mL, represented by the linear equation y=-656.83x+710.43, with a linear correlation coefficient of R2=0.9968. This method is expected to be applicable to the detection of human serum samples. The use of willow leaves gives the CQDs a quantum yield of 12.1% only. Therefore, a novel phosphorus-doped biomass CQDs (P-BCQDs) fluorescent probe was designed. The addition of sodium pyrophosphate gives the quantum yield as high as 25.4%. The P-BCQDs exhibit a response time of 2 minutes for the detection of Hg²⁺ at a pH of 7, with concentrations of Hg²⁺ ranging from 0 to 20 µmol/L. A linear relationship between the F0/F of the P-BCQDs and Hg2+ concentration was established, with a detection limit of 9 nmol/L. Notably, the fluorescence of the P-BCQDs-Hg²⁺ system gradually increased with the concentration of glutathione (GSH) ranging from 0 to 10 μmol/L. This method is expected to enable the simultaneous detection of intracellular Hg2+ and GSH. Finally, to enhance the quantum yield and to address the issue of low detection accuracy associated with a single fluorescent probe, a novel ratiometric fluorescent probe was developed by incorporating gold nanoclusters (AuNCs). CQDs with a quantum yield of 27.6% were synthesized using non-toxic, chemically rich apricot leaves as raw materials. These CQDs were then combined with GSH-conjugated AuNCs, which were synthesized through the GSH reduction of chloroauric acid to, form an AuNCs/CQDs ratio fluorescent probe. The quantitative detection of Cu(II) was accomplished through visual analysis of colour change and the ratio of emission peak intensities. During the reaction, the probe changed colour from pink to purple to blue at varying concentrations of Cu(II). The linear range of the AuNCs/CQDs ratiometric fluorescent probe for Cu(II) was 0-120 µmol/L, and the limit of detection was 0.65 µmol/L. This method is intended for the visual detection of intracellular Cu(II).